The impact of New Zealand's disclosure reform on differential managerial disclosure behaviour for good news versus bad news firms - Poskitt, Russell; Wang, Y.; Marsden, A. (Emerald Group Publishing, 2011)
Purpose – The purpose of this paper is to investigate the impact of the introduction of New Zealand's statutory-backed continuous disclosure regime enacted in December 2002 on the differential disclosure behaviour of New Zealand firms with good and bad earnings news. Design/methodology/approach – This paper examines the level of information disclosure, analyst forecast error and forecast dispersion, abnormal returns and abnormal volumes for firms with good and bad news earnings announcements in a sample period surrounding reforms to New Zealand's continuous disclosure regime. Findings – The authors find evidence that the pre-announcement information flow was poorer prior to the reform for bad news firms compared to good news firms, in terms of greater analysts' forecast dispersion and a larger abnormal price reaction to the actual earnings announcement. Second, the reform reduced the asymmetry of information flow between good and bad news firms, with the differences in analysts' forecast dispersion and abnormal price reaction dissipating after the reform. Research limitations/implications – The findings suggest that the reforms to New Zealand's continuous disclosure regime have reduced managers' propensity to withhold bad news and improved the quality of information provided to investors by firms with bad earnings news. Originality/value – This study improves our understanding of the impact of disclosure reform on the behaviour of managers in a market with relatively low liquidity and less litigation risk in comparison to larger and more developed markets.